Marketing Strategy for Cowhide Crackers in Cakranegara District, Mataram City - Rahmayani, Alfia; Anwar, Khairil; Muhsin, Muhsin (Pascasarjana Universitas Pasundan, 2023)
Marketing strategy is one way to win sustainable competitive advantage for companies that produce goods or services.The strategy that has received a lot of attention from the cowhide cracker business is product strategy and promotional strategy. Cowhide crackers in Cakranegara District is a cowhide cracker industry that produces cowhide crackers by providing very interesting flavors and shapes or sizes of cowhide crackers. The aim is to determine the influence of product strategy and promotional strategy, both simultaneously and partially, on demand for Cowhide Crackers products in Cakranegara District, Mataram City.The method used in this research is the Discreptive Method with survey techniques. From the population of SMEs in the cowhide cracker industry in Cakranegara District, 30 traders were taken as respondents. The data obtained was processed in the form of a Likert Scale and analyzed using Multiple Regression Analysis using SPSS (Statistical Package for the Social Sciences) Version 20. Based on the results and analysis of research results, it can be concluded that:1)Respondents' perceptions of demand for cowhide cracker products are classified as medium criteria (81 - 113) with an average demand of 101.60 per person in a six month period. The distribution of respondents based on the demand score criteria is: Low demand as much as8 (26.7%), medium demand 7 people (23.3%) and high demand 15 people (50%). While pRespondents' perception of the performance of Marketing Strategy and Product Strategy is classified as High, 2)The multiple linear regression model (Multiple Linear Regression) between Product Strategy and Promotion Strategy on Product Demand is: Y = 7.496+ 0.313X1 +0.062X2, where: Y = Product Demand X1= Product Strategy and X2= Promotion Strategy, 3) Based on Test F (Anova) can be concluded that Fcount (3.55) > Ftable (3.34), and the significance level of 0.043 is smaller than 0.05. This means that Ho is rejected and H1 is accepted, thus Product Strategy (X1) and Promotion Strategy (X2) simultaneously have a significant effect on Demand for Cowhide Crackers (Y), 4) Further test (Post Test) with t test (partial influence test ) shows that: Product Strategy has a significant effect on Product Demand, while Promotion Strategy has no significant effect on Product Demand. This is indicated by the significance value of Product Strategy Anova being smaller than 0.05, namely 0.034. Meanwhile, the Anova significance value of Promotion Strategy is greater than 0.05, namely 0.684, 5) Coefficient of Determination) between Product Strategy and Promotion Strategy on Product Demand is 0.208. This means that Product Strategy and Promotion Strategy simultaneously have an influence of 20.8% on the Demand for Cowhide Crackers (Y), while other variables that are not included in this research variable have an influence of 79.2%..